Equations of state and PVT analysis : applications for improved reservoir modeling - Ahmed, Tarek H., 1946- (Gulf Professional Publishing, an imprint of Elsevier, 2016)
Understanding the properties of a reservoir's fluids and creating a successful model based on lab data and calculation are required for every reservoir engineer in oil and gas today, and with reservoirs becoming more complex, engineers and managers are back to reinforcing the fundamentals. PVT (pressure-volume-temperature) reports are one way to achieve better parameters, and Equations of State and PVT Analysis, 2nd Edition, helps engineers to fine tune their reservoir problem-solving skills and achieve better modeling and maximum asset development. Designed for training sessions for new and existing engineers, Equations of State and PVT Analysis, 2nd Edition, will prepare reservoir engineers for complex hydrocarbon and natural gas systems with more sophisticated EOS models, correlations and examples from the hottest locations around the world such as the Gulf of Mexico, North Sea and China, and Q&A at the end of each chapter. Resources are maximized with this must-have reference.
Keywords: Reservoir oil pressure -- Mathematical models.; Phase rule and equilibrium -- Mathematical models.; Petroleum -- Underground storage.; elektronické knihy; electronic books